PERENCANAAN PENGECATAN PADA DERMAGA APUNG KAPAL SELAM DI DAERAH NATUNA DENGAN MENGGUNAKAN CPM PDM PERT (STUDI KASUS PT. WAHYU AGUNG) - Adam Erlanda Syarif Dzaky Adam; Intan Baroroh (JURNAL JALASENA, 2023)
In the floating dock construction project, it is required to work quickly according to schedule Project planning frequently does not go as expected when floating dock construction projects are carried out. Therefore, the conditions of the shipyard are followed when planning the construction of a floating wharf. In this study, Pontoon 2 at PT. Great Revelation's submarine floating dock will be painted, and its painting will be analyzed using the CPM PDM PERT method. The three methods' networks were planned, and the Project Evaluation and Review Technique (PERT) method's results showed that it took less time overall. The planning model created by the researchers only took 43.81 hours, and it had a 99.31% chance of successfully painting the floating dock. Because the PERT method has three time variances to achieve the expected time, it can be said that it can be used in one project activity in detail.